INTERAKSI BIROKRASI PEMERINTAH DALAM PEMBANGUNAN DI DAERAH PESISIRAN MUNCAR KABUPATEN BANYUWANGI - DWI AYU ITA PURNAMASARI (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2018)
This research is motivated by a tendency shown by NGOs, namely their clear vision and mission began to side with community development. During the New Order era, their existence was more positioned as an institution that always inconvenienced every government policy. Synergy or good cooperation patterns between the Government Bureaucracy and LPIP (NGOs) are very important in empowering coastal communities. The purpose of this study is to obtain accurate information about the community's response to the development efforts carried out by the government and NGOs. The research method used in this research is descriptive qualitative research. The results showed that: 1). LPIP NGOs in dealing with several conflicts offer a different approach, namely using an approach strategy that places the community as the main actor by involving them (community leaders, bureaucracy, entrepreneurs) as mediators